Canva and Comic Strips: Facilitate on Teaching Writing Instruction - Widiarti, Yenni; Jamilah (International Journal of Contemporary Studies in Education, 2024)
The purpose of this study is to examine the use of Canva and comic strips as instructional tools for enhancing writing proficiency in the class of XI-9 at SMA Negeri 7 Purworejo. This study aims to develop efficacious and innovative pedagogical approaches that align with students' learning objectives by investigating the utilization of comic strips and Canva as tools for enhancing writing proficiency. The present study conducted utilizing the CAR (classroom action research) methodology. The study revealed that the utilization of comic strips and Canva has a substantial positive impact on the enhancement of pupils' writing abilities. The students exhibited increased exploratory behaviour following the utilization of comic strips and Canva for writing. The researchers made efforts and obtained numerous findings from the media. Canva exerts a significant impact on fostering creativity and enhancing the engagement of pupils in writing tasks, leading to heightened interest and motivation among students to develop their writing skills. Concurrently, comic strips play a role in enhancing students' competencies in various domains, including grammar, vocabulary, and organization.